HUBUNGAN MOTIVASI BERPRESTASI SISWA DENGAN HASIL BELAJAR PENDIDIKAN JASMANI - Helmy Firmansyah (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2009)
The purpose of this research was to examine the correlation between the student learning motivation and physical education learning outcomes. This research involved 120 third graders Sekolah Dasar Merdeka, Bandung. It employed survey using simple, multiple, and partial regression analysis. The hipothesis showed that there was a positif correlation between student motivation and student learning outcomes in physical education. Kata Kunci: motivasi berprestasi, hasil belajar pendidikan jasmani